Design of L-Band Multiwavelength Laser for TDM/WDM PON Application - Nani Fadzlina Naim; Muhammad Amirul Hafiz Mohamed Hashim; Suzi Seroja Sarnin; Norsuzila Ya'acob; Latifah Sarah Supian (مجلة بغداد للعلوم)
This paper presents on the design of L-Band Multiwavelength laser for Hybrid Time Division Multiplexing/ Wavelength Division Multiplexing (TDM/WDM) Passive Optical Network (PON) application. In this design, an L-band Mulltiwavelength Laser is designed as the downstream signals for TDM/WDM PON. The downstream signals ranging from 1569.865 nm to 1581.973 nm with 100GHz spacing. The multiwavelength laser is designed using OptiSystem software and it is integrated into a TDM/WDM PON that is also designed using OptiSystem simulation software. By adapting multiwavelength fiber laser into a TDM/WDM network, a simple and low-cost downstream signal is proposed. From the simulation design, it is found that the proposed design is suitable to be used in TDM/WDM PON for up to 64 Optical Network Units (ONUs).